Federalism and Australia's National Health and Health Insurance System - Andrew Podger (ACHSM, 2016)
While health reform in Australia has been marked by piecemeal, incremental changes, the overall trend to increasing Commonwealth involvement has not been accidental or driven by power-hungry centralists: it has been shaped by broader national and international developments including technological change and the maturing of our nation and its place internationally, and by a widespread desire for a national universal health insurance system. In many respects the Australian health system performs well, but the emerging challenges demand a more integrated, patient-oriented system. This is likely to require a further shift towards the Commonwealth in terms of financial responsibility, as the national insurer. But it also requires close cooperation with the States, who could play a firmer role in service delivery and in supporting regional planning and coordination. The likelihood of sharing overall responsibility for the health system also suggests there is a need to involve the States more fully in processes for setting national policies. This article draws heavily on a lecture presented at the Australian National University in October 2015. It includes an overview of Australia's evolving federal arrangements and the context within which the current Federalism Review is being conducted. It suggests Australia will not return to 'coordinate federalism' with clearly distinct responsibilities, and that greater priority should be given to improving how we manage shared responsibilities. There is a long history of Commonwealth involvement in health, and future reform should build on that rather than try to reverse direction. While critical of the proposals from the Commission of Audit and in the 2014 Budget, the lecture welcomed the more pragmatic approaches that seemed to be emerging from the Federalism Review discussion papers and contributions from some Premiers which could promote more sensible measures to improve both the effectiveness and the financial sustainability of Australia's health and health insurance system. The Commonwealth's new political leadership in 2015 seemed interested in such measures and in moving away from the Abbott Government's approach. But the legacy of that approach severely damaged the Turnbull Government in the 2016 federal election as it gave traction to Labor's 'Mediscare' campaign. In addition to resetting the federalism debate as it affects health, the Turnbull Government now needs to articulate the principles of Medicare and to clarify the role of the private sector, including private health insurance, in Australia's universal health insurance system. Labor also needs to address more honestly the role of the private sector and develop a more coherent policy itself. Abbreviations: COAG - Council of Australian Governments; NHHRC - National Health and Hospitals Reform Commission; PHI - Private Health Insurance; VFI - Vertical Fiscal Imbalance.